Rabies virus neutralizing activity, pharmacokinetics, and safety of the monoclonal antibody mixture SYN023 in combination with rabies vaccination: Results of a phase 2, randomized, blinded, controlled trial. Issue 40 (24th September 2021) - McClain, J. Bruce; Chuang, Ariel; Reid, Caroline; Moore, Susan M.; Tsao, Eric
Highlights: Protection appears earlier with SYN023 vs serum-derived immunoglobulin regimen. SYN023 associated with limited suppression of vaccine response. Safety profile of SYN023 post-exposure prophylaxis regimens is mild and manageable. Abstract: Background: SYN023-002 is a randomized, blinded, controlled study comparing rabies virus neutralizing activity (RVNA) and safety of SYN023, a monoclonal anti-rabies antibody mixture, to human-serum derived anti-rabies immunoglobulin (RIG) when administered with commercially available vaccines to healthy adult volunteers. Methods: Participants were randomized among 4 treatment groups (SYN023 + Imovax, SYN023 + RabAvert, HyperRab + Imovax, HyperRab + RabAvert). On Day 0, subjects received 1 dose of RIG (0.3 mg/kg SYN023 or 20 IU/mL HyperRab) and their first of 5 vaccine doses. The primary objective was to compare cumulative RVNA between SYN023 and HyperRab recipients. Secondary objectives were to compare safety and to assess SYN023 pharmacokinetics and immunogenicity. Results: All 164 randomized subjects initiated treatment and were included in safety analyses. At least 34 subjects/treatment group received all treatment and had complete RVNA results, thus were included in the primary endpoint analysis. Mean RVNAs were approximately ten-fold higher in SYN023 recipients compared to HyperRab recipients until Day 14. From Day 14 onwards, mean RVNA was lower in SYN023 recipients, but remained above the RVNA level widely considered adequate (≥0.5 IU/mL) through Day 112 (study end). The point estimate of the cumulative RVNA (83.22% SYN023/HyperRab), but not the lower CI bound (90% CI: 66.06%, 104.83%), fell within the protocol-defined similarity margin. Each RIG + vaccine regimen appeared safe with mostly mild AEs and no serious or severe related events observed. Except injection site pain (22% HyperRab recipients vs. 6% SYN023 recipients), treatment-related AEs incidences were similar between RIGs. Anti-SYN023 antibodies were observed but had no apparent effects on PK or safety. Conclusions: SYN023 administered with commercially available vaccines provides adequate antibody coverage beginning earlier than other commercially available RIGs with an acceptable safety profile. Some suppression of vaccine response occurred, but RVNA levels ≥ 0.5 IU/mL were maintained throughout the relevant period. Registration: ClinicalTrials.gov #NCT02956746. Funding: Synermore biologics.